Evaluating the implications of Brexit for research collaboration and policy: a network analysis and simulation study. Issue 9 (10th September 2019) - Garas, George; Cingolani, Isabella; Patel, Vanash M; Panzarasa, Pietro; Darzi, Ara; Athanasiou, Thanos
Abstract : Objective: To evaluate the role of the European Union (EU) as a research collaborator in the UK's success as a global leader in healthcare research and innovation and quantify the impact that Brexit may have. Design: Network and regression analysis of scientific collaboration, followed by simulation models based on alternative scenarios. Setting: International real-world collaboration network among all countries involved in robotic surgical research and innovation. Participants: 772 organisations from industry and academia nested within 56 countries and connected through 2397 collaboration links. Main outcome measures: Research impact measured through citations and innovation value measured through the innovation index. Results: Globally, the UK ranks third in robotic surgical innovation, and the EU constitutes its prime collaborator. Brokerage opportunities and collaborators' geographical diversity are associated with a country's research impact (c=211.320 and 244.527, respectively; p<0·01) and innovation (c=18.819 and 30.850, respectively; p<0·01). Replacing EU collaborators with US ones is the only strategy that could benefit the UK, but on the condition that US collaborators are chosen among the top-performing ones, which is likely to be very difficult and costly, at least in the short term. Conclusions: This study suggests what has long been argued, namely that the UK-EU research partnership has been mutually beneficial and that its continuation represents the best possible outcome for both negotiating parties. However, the uncertainties raised by Brexit necessitate looking beyond the EU for potential research partners. In the short term, the UK's best strategy might be to try and maintain its academic links with the EU. In the longer term, strategic relationships with research powerhouses, including the USA, China and India, are likely to be crucial for the UK to remain a global innovation leader.